Cenozoic pelagic accumulation rates and biased sampling of the deep-sea record - J. Renaudie; D. B. Lazarus (Biogeosciences)
Global weathering is the primary control of the Earth's climate over geologic timescales, converting atmospheric pCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="19d363e4a348c056939d011626862cf3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-1929-2025-ie00001.svg" width="24pt" height="12pt" src="bg-22-1929-2025-ie00001.png"/></svg:svg> into dissolved bicarbonate, with carbon sequestration by marine plankton as carbonate and organic carbon on the ocean floor. The accumulation rate of pelagic marine biogenic sediments is thus an indication of weathering history. Previous studies of Cenozoic pelagic sedimentation have yielded contrasting results, though most show a dramatic rise (up to 6 times) in rates over the Cenozoic. This contrasts with model expectations for approximate steady state in weathering, pCO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="f970a075afd747993d97d753129f4038"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-1929-2025-ie00002.svg" width="24pt" height="12pt" src="bg-22-1929-2025-ie00002.png"/></svg:svg>, and sequestration over time. Here we show that the Cenozoic record of sedimentation recovered by deep-sea drilling has a strong, systematic bias towards lower rates of sedimentation with increasing age. When this bias is removed, accumulation rates are shown to actually decline by ca. 2 times over the Cenozoic. However, when accumulation area is adjusted for changes in available deposition area, global sediment flux to the deep sea is shown to have nearly doubled at the Eocene–Oligocene boundary but was otherwise essentially constant. Compilations of other metrics correlated to sedimentation rate (e.g. productivity, biotic composition) also must have a strong age bias, which will need to be considered in future paleoceanographic studies.